Analisis Pengaruh Pengaruh Gaya Kepemimpinan, Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan PT Permodalan Nasional Madani Persero Unit Lawang (Studi Kasus Pada Kinerja Karyawan PT Permodalan Nasional Madani Persero Unit Lawang ) - Fitriyah, Hanis; Arifin, Rois; Rahmawati, Rahmawati (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the influence of Leadership Style, Work Discipline and Work Motivation on Employee Performance. The object of this research is PT Permodalan Nasional Madani (Persero) with a sample size of 95. The sampling technique uses purposive sampling. Data collection techniques use questionnaires and data analysis tools. Based on the results of partial research analysis, leadership style has a significant effect on employee performance. Meanwhile, partially Work Discipline has a significant effect on employee performance. Meanwhile, partially motivation has a significant effect on employee performance. Keywords: Leadership Style, Work Discipline, Work Motivation and Employee Performance